Electrical transport properties of p‐type 4H‐SiC. Issue 4 (15th November 2016) - Contreras, Sylvie; Konczewicz, Leszek; Arvinte, Roxana; Peyre, Hervé; Chassagne, Thierry; Zielinski, Marcin; Juillaguet, Sandrine
Abstract : The Hall hole density p H and Hall mobility μ H in highly aluminum‐doped 4H‐SiC have been investigated in the wide temperature range between 100 and 900 K. After an overview of the literature data related to the analysis of electrical transport experiments, a model taking into account the two uppermost valence bands of heavy and lights holes, one single acceptor energy E A and the empirical Hall factor r Hexp has been discussed in details. The limits of the applied model as a function of temperature and acceptor concentration have been considered. For each analyzed sample, the acceptor density N A and the compensation ratio N D /N A have been experimentally assessed by capacitance–voltage and secondary ion mass spectroscopy measurements. Finally, the Hall carrier concentration vs. doping level N A − N D as well as ionization energy of acceptor E A vs. acceptor concentration N A in 4H‐SiC have been discussed.